Assessment and Management of Risk for Intimate Partner Violence by Police Officers Using the Brief Spousal Assault Form for the Evaluation of Risk. (February 2014) - Storey, Jennifer E.; Kropp, P. Randall; Hart, Stephen D.; Belfrage, Henrik; Strand, Susanne
The management of intimate partner violence (IPV) typically falls to police. For assistance, officers are increasingly using violence risk assessment tools like the Brief Spousal Assault Form for the Evaluation of Risk (B-SAFER). This study replicates the methodology of Belfrage et al. but examines the B-SAFER as used by Swedish police officers when assessing and managing IPV. Results revealed a positive relationship between risk and management. Total scores and overall risk ratings predicted recidivism (AUC [Area under the curve] = .70 and .69, respectively). Finally, a pattern where management recommendations were associated with decreased recidivism in high risk perpetrators but increased recidivism in low risk perpetrators was found. Results validate the use of the B-SAFER by police and reveal mostly comparable findings between the B-SAFER and the Spousal Assault Risk Assessment Guide, as examined by Belfrage et al., but suggest that the B-SAFER may be better suited for police.